1998
DOI: 10.1103/physrevb.58.r10151
|View full text |Cite
|
Sign up to set email alerts
|

Excitation transfer in self-organized asymmetric quantum dot pairs

Abstract: Excitation transfer processes within self-organized quantum dot ͑QD͒ pairs in bilayer InAs/GaAs QD samples are investigated. QDs in samples with a 1.74-ML InAs seed layer and a 2.00 ML InAs second layer are found to self-organize in pairs of unequal sized QDs with clearly discernible ground-state transition energy. Photoluminescence ͑PL͒ and PL excitation results for such asymmetric QD pairs provide evidence for nonresonant energy transfer from the smaller QDs in the seed layer to the larger QDs in the second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
85
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 15 publications
(24 reference statements)
6
85
0
2
Order By: Relevance
“…In addition, there is a small blue-shift of both peaks of the PL from sample B in comparison with sample A. This is likely due to the change of the confinement potential resulting from the addition of the Al 0.5 Ga 0.5 As barrier [24].…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, there is a small blue-shift of both peaks of the PL from sample B in comparison with sample A. This is likely due to the change of the confinement potential resulting from the addition of the Al 0.5 Ga 0.5 As barrier [24].…”
Section: Resultsmentioning
confidence: 88%
“…Here, it is also found that the separation between the bottom of TQDs and the tip of the SQDs is only 2~3 nm. Such a thin GaAs barrier will lead to strongly electronic coupling and hence interlayer carrier transfer from the small SQDs to the large TQDs [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…When the barriers are thin enough in the stacked QD system, the carrier tunneling transfer becomes significant, which was previously studied by various authors. 5,6,7,8 However, their results on the barrier thickness dependence of the transfer time are quite different from each other.…”
mentioning
confidence: 82%
“…During the last decade, a great effort has been made studying the temperature evolution of QD emission, obtaining good agreements between experimental data and kinetic exciton recombination models [4]. Thermal escape through the wetting layer (WL) or by phonon assisted tunneling is usually claimed as the most suitable mechanism to describe carrier transfer between QDs both in monomodal and bimodal distributions [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, a great effort has been made studying the temperature evolution of QD emission, obtaining good agreements between experimental data and kinetic exciton recombination models [4]. Thermal escape through the wetting layer (WL) or by phonon assisted tunneling is usually claimed as the most suitable mechanism to describe carrier transfer between QDs both in monomodal and bimodal distributions [5][6][7].In the present study we have analyzed this phenomenon in two different samples containing very low density of InAs/GaAs QDs. This is important because we can separate the μPL spectra from different QDs within the illumination area and hence compare more directly microscopic and ensemble exciton recombination dynamics.…”
mentioning
confidence: 99%